TOWARDS TIME-RESOLVED DIFFRACTION STUDIES WITH GLYCOGEN-PHOSPHORYLASE - Duke, E; Hadfield, A; Martin, J; Clifton, I; Hajdu, J; Johnson, L; Reid, G; Trentham, D; Bruce, I; Fleet, G (1991)
Laue diffraction with high intensity, broad-spectrum synchrotron radiation sources allows three-dimensional data sets on protein crystals to be recorded in seconds or milliseconds and opens the way for time-resolved studies on dynamic events in crystals. This chapter briefly reviews the field and describes progress towards time-resolved studies with glycogen phosphorylase. Methods for the synchronization of the start of reaction with the start of data collection have been developed for the phosphorolytic reaction of glycogen phosphorylase. The compound 3,5-dinitrophenylphosphate is photolabile, yielding Pi and the by-product, 3,5-dinitrophenol, which is non-reactive with the enzyme. Spectroscopic studies show that the compound has good quantum yield and that photolysis is rapid (greater than 1000 s-1). Release of the dinitrophenylate anion, following a pulse of light from a xenon flash lamp, has been monitored with a diode array spectrophotometer specially adapted for measurements on crystals. In a laboratory X-ray experiment with crystals of glycogen phosphorylase b, release of Pi and formation of the enzyme-product complex have been demonstrated. The way is now open for Laue diffraction studies on the catalytic reaction in the crystal.